A broad-applicability method for mercury speciation in various seafoods using microwave-assisted extraction and ion chromatography-inductively coupled plasma mass spectrometry. Issue 14 (21st March 2023) - Li, Ruiling; Pan, Yuquan; Sun, Chaochen; Lin, Chen; Chen, Shilong; Wu, Yongning; Fu, FengFu
Abstract : Almost all marine organisms contain both inorganic and organic mercury, and thus it is extremely important to determine mercury species in seafood to objectively and scientifically assess the health risk posed by mercury. Abstract : Almost all marine organisms contain both inorganic and organic mercury, and thus it is extremely important to determine mercury species in seafood to objectively and scientifically assess the health risk posed by mercury. We herein developed a broad-applicability microwave-assisted extraction method and a robust ion chromatography-inductively coupled plasma mass spectrometry (IC-ICP-MS) method for the speciation analysis of mercury in various seafood samples including seaweeds, fishes and shellfishes. The extraction method has broad adaptability, it can be used to simultaneously extract mercury species from various seafood samples including seaweeds, fishes and shellfishes without altering the chemical species of mercury, with an extraction efficiency >90%. Especially, the seafood extract obtained with the extraction method can be directly used for the following IC-ICP-MS determination of mercury species without additional pretreatment. The IC-ICP-MS method used low-cost cation guard columns as the separation column, and has an instrument detection limit of 0.02–0.05 ng mL −1 for Hg 2+, CH3 Hg + and C2 H5 Hg + . The developed extraction and IC-ICP-MS methods have been successfully used to determine Hg 2+, CH3 Hg + and C2 H5 Hg + in various seaweeds, fishes and shellfishes without the matrix effect, with a method detection limit of 2.4–6.0 ng g −1 dried weight, a recovery of 92–105%, and a relative standard deviation (RSD, n = 5) of less than or equal to 6%. The success of this study offers a reliable and universal approach for the speciation analysis of mercury in seafood, which may provide the database for objectively assessing the health risks of mercury in seafood and ensuring the safety of consumption of seafood.